VD_FINDINFO HC / 2011 / 489 vom 1. September 2011 - VD Tribunal cantonal (2011)
PROTECTION DE L'UNION CONJUGALE, OBLIGATION D'ENTRETIEN, COMPÉTENCE INTERNATIONALE | 176 al. 1 CC, 176 al. 3 CC, 10 LDIP